2011
DOI: 10.4061/2011/761891
|View full text |Cite
|
Sign up to set email alerts
|

Does EEG Montage Influence Alzheimer′s Disease Electroclinic Diagnosis?

Abstract: There is not a specific Alzheimer's disease (AD) diagnostic test. AD diagnosis relies on clinical history, neuropsychological, and laboratory tests, neuroimaging and electroencephalography. Therefore, new approaches are necessary to enable earlier and more accurate diagnosis and to measure treatment results. Quantitative EEG (qEEG) can be used as a diagnostic tool in selected cases. The aim of this study was to answer if distinct electrode montages have different sensitivity when differentiating controls from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Lastly, it was also observed that high accuracy and sensitivity levels could be obtained with the bipolar signals alone. Since the bipolar montage measures EEG regional potentials [10], an interhemispheric disconnect may indeed be present with AD.…”
Section: B Classifier Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, it was also observed that high accuracy and sensitivity levels could be obtained with the bipolar signals alone. Since the bipolar montage measures EEG regional potentials [10], an interhemispheric disconnect may indeed be present with AD.…”
Section: B Classifier Performancementioning
confidence: 99%
“…An EEG bipolar signal was obtained by subtracting the two bi-auricular referenced signals involved [10]. The following bipolar channels were used in this study: F3-F4, F7-F8, C3-C4, T3-T4, P3-P4, T5-T6, and O1-O2.…”
Section: A Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by previous findings [23,24], we explore the use of support vector machines (SVM) for feature selection and classification. A complete description of these steps is beyond the scope of this paper and the interested reader is referred to [25] and [26] for more details on SVMs.…”
Section: Feature Selection and Classifier Designmentioning
confidence: 99%
“…Previous findings have suggested that i) EEG spectral power is reduced with AD in the alpha (8)(9)(10)(11)(12) and beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) frequency bands, and increased in the delta (0.1-4 Hz) and theta (4-8 Hz) bands [7], ii) spectral coherence is decreased between the two hemispheres in the alpha and beta frequency bands [8], and iii) EEG pattern complexity [9][10][11] is reduced. More recently, a new promising biomarker was developed, which was termed "percentage modulation energy" (PME) [12].…”
Section: Introductionmentioning
confidence: 99%